CHALLENGES IN PERSPECTIVE ON CORPORATE STRATEGY - Ande, Diin Fitri; Dahlan, Rolan Mauludy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
There are several issues in corporate strategies such as the impact of corporate to performance, the cause and limit of performance, development management and external environment of corporation. This study aims to discuss those issues based on literature review. It is found out that corporate impact to performance is non-neglectable, event though the degree of impact is still unknown. Experience managerial service are important for company to achieve its performance and to achieve its performance, corporation may choose between two approaches incremental and comprehensive, each approach has its own benefits and drawbacks. As a result, it should be aligned with internal and external condition of the corporation and the cost and benefit aspects. External aspect of the corporation in this particular, macroeconomic uncertainty, will influence the strategy of corporation even when the firm only play in local market. In addition, national economic development will impact on how corporation build its strategy.Keywords: corporate strategy, corporate-impact, corporate performance.